ANALISIS PERATURAN MENTERI PENDIDIKAN KEBUDAYAAN RISET DAN TEKNOLOGI RI NOMOR 12 TAHUN 2024: IMPLIKASI TERHADAP PROGRAM PELAYANAN PENDIDIKAN KHUSUS DI YAYASAN ARROYYAN CORDOBA - Qomarudin Khaqiqi, Irfan; Wasliman, Iim; Andriana Gaffar, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Indonesian Ministerial Regulation on Education, Culture, Research, and Technology No. 12 of 2024 regarding inclusive education at the Arroyyan Cordoba Foundation. Employing a descriptive qualitative approach with a case study method, the research focuses on planning, organizing, implementing, and monitoring special education programs. Data were collected through in-depth interviews, direct observations, and document studies. The findings reveal that need-based planning involving various stakeholders resulted in an inclusive curriculum and routine teacher training. The organization is supported by efficient structures, cross-party collaboration, and active parental involvement. Program implementation includes Individualized Educational Programs (IEP), extracurricular activities promoting holistic student development, and the use of educational technology. Data-driven monitoring mechanisms ensure program sustainability. This study concludes that high-quality inclusive education can be achieved through collaboration among the government, foundations, and society.Keywords: inclusive education, educational policy, special education, education management.